Organização do território e fiscalidade régia em Portugal: as origens (Sécs. XII-XIV) - Sottomayor-Pizarro, José Augusto de (2021)
This paper shows how the Portuguese nobility never had a significant territorial or political expression, capable of contradicting the centralization policy of Portuguese kings. It starts with a review of the evolution of the conquest and construction of the kingdom of Portugal, almost always under the initiative of the crown, and continues with the means with which the Portuguese monarchs imposed, from the beginning, a continued policy of strengthening their power. A study of the Inquirições Gerais (General Inquiries), one of the most effective instruments used by the Portuguese monarchs from the beginning of the thirteenth to the middle of the fourteenth century to evaluate assets and control seignorial abuses, will help us to understand how the patrimony of the Portuguese aristocracy was managed.